IMPLEMENTASI KEBIJAKAN DAN STRATEGI MANAJEMEN RISIKO DI BADAN USAHA MILIK NEGARA: KAJIAN PUSTAKA MENGENAI OPTIMALISASI SIKLUS PLAN-DO-CHECK-ACT (PDCA), RISK APPETITE FRAMEWORK, DAN KEY RISK INDICATORS (KRI) DALAM PENGUATAN KAPABILITAS, KEPATUHAN, DAN KEBERLANJUTAN OPERASIONAL BUMN - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2026)
This study examines the implementation of risk management policies and strategies in State-Owned Enterprises (SOEs) through the optimisation of the Plan-Do-Check-Act (PDCA) cycle, Risk Appetite Framework (RAF), and Key Risk Indicators (KRI) based on a literature review approach. The study found that the integration of these three elements strengthens organisational capabilities through a continuous learning process, improves regulatory compliance in accordance with PER-1/MBU/2011 and ISO 31000, and ensures operational sustainability amid economic and ESG disruptions. The impact includes reduced performance volatility, increased ROE, and post-crisis resilience, with the main challenges being cultural resistance and technological limitations. Strategic recommendations include the formation of a Risk Committee, an AI-based KRI dashboard, and policy standardisation by the Ministry of State-Owned Enterprises for the transformation of state-owned enterprises towards agile and accountable governance.